Competency-Based Curriculum Development in Islamic Religious Education: Integrating Spiritual Values and 21st-Century Competencies - Amin Ruksin; Muhammad Agus Salim; Muhammad Zaironi (Journal of Practice Learning and Educational Development, 2026)
The transformation of global education necessitates the development of curricula that are responsive to twenty-first-century dynamics without neglecting spiritual and moral dimensions. This conceptual article aims to analyze and formulate an integrative framework for competency-based curriculum development in Islamic Religious Education (IRE) that synergizes spiritual values with twenty-first-century competencies. Employing a systematic-critical literature review of recent international scholarship (2021–2025), this article identifies a critical gap between conventional competency-based curriculum paradigms, which tend to be instrumentalistic, and the need for holistic human development. The conceptual findings indicate that the integration of Islamic spiritual values encompassing tauhid, akhlaq, and maqashid al-shariah with key competencies such as the 4Cs (critical thinking, creativity, collaboration, and communication), digital literacy, and global character is not dichotomous but mutually reinforcing in fostering comprehensive competencies. This article proposes a conceptual model, the Spiritual-Competency Integration Framework, which positions Islamic Religious Education as a foundation for holistic curriculum development with global relevance. The theoretical implications include a reorientation of the epistemology of IRE curricula toward an integrative-transformative approach, while the practical implications provide guidance for curriculum design, pedagogy, and assessment grounded in spiritual–twenty-first-century competencies